The slave sublime: the language of violence in Caribbean literature and music - Lettman, Stacy J. (University of North Carolina Press, 2022)
The slave sublime: a Jamaican case study -- A trickster's challenge to rationalism: Andrew Salkey's discourse of the imagination in "A quality of violence" -- Language and social death: boundary-crossing and the grammar of violence in NourbeSe Philip's prose and poetry -- The changing same for I-an-I in Babylon: Bob Marley's representations of the slave sublime in postcolonial Jamaica -- The real (and) ghetto life: excess violence and Manichean delirium in Marlon James's "A brief history of seven killings" -- The Ogun archetype in Jamaican dancehall music: harnessing Ogun's combative will to challenge globalization's Dionysiac nature.